CEOs, leaders and managing mental health: a tension-centered approach. Issue 15 (22nd August 2021) - Quinane, Erin; Bardoel, E. Anne; Pervan, Simon
Abstract: Little is known about how leaders view their role in managing employee mental health (MH). In response, interviews were conducted with 26 Australian CEOs and senior leaders from the private, public, and non-profit sectors across many industries. Qualitative analysis of the interviews identified themes including viewing employee MH as an individual issue, awareness of implicit bias, creating a safe workplace, ignorance of employee MH and best practices, a belief in the value of caring, use of a broad array of programs, and institutional/contextual factors influencing employee MH. A tension-centered approach was used to understand the themes. Tensions found include privacy concerns and managerial ignorance as opposed to employees feeling free to disclose MH information and finding safety and compassion in responses to employee disclosure; that tension can lead to a cycle of ignorance feeding ignorance. Other tensions include whether the organization cannot or can help mental ill health and whether MH is an individual or social/organizational responsibility. Theoretical contributions include identifying potential overlap between various responses to tensions, and caveats regarding the ostensible superiority of one type of response (synthesis). Practical recommendations include the promotion of workplace cultures supportive of disclosure/compassion/safety, and developing metrics to monitor Employee Assistance Programs (EAPs).